Restaurant Tax Collection and Contribution Mechanism to Regional Original Income in Cilegon City - Refi Pratiwi; Farhan Ikhlasul Amal; Intan Puspanita (PT. EQUATOR SINAR AKADEMIA, 2022)
Cilegon City is a city in Banten Province. Cilegon City has a fairly high level of economy in the management of industry, trade, and other management. The Regional Financial and Asset Management Agency (BPKAD) of Cilegon City stipulates various types of taxes and one of the taxes that provides a fairly high revenue is the restaurant tax. The increasing number of restaurants in Cilegon City can be used as potential in an effort to increase regional revenues from restaurant taxes. Although the number of restaurant taxpayers continues to increase every year, there are still taxpayers who are in arrears on their taxes so that they get a warning letter as a form of sanction, while the number of taxpayers who receive a warning letter is 235 restaurant taxpayers. The purpose of this study was to find out how the mechanism for collecting restaurant taxes at the Regional Financial and Asset Processing Agency (BPKAD) of Cilegon City and to determine the contribution of restaurant taxes to Cilegon City's Original Regional Revenue. The mechanism for collecting restaurant taxes at the Regional Financial and Asset Management Agency of Cilegon City has been carried out with a self-assessment system in accordance with Mayor Regulation Number 50 of 2011 concerning Collection of Restaurant Taxes. The percentage of the contribution obtained falls into the small criteria but is sufficient to provide a small contribution to Cilegon City's Original Regional Revenue (PAD). The small contribution is due to several influencing factors, such as entrepreneurs or restaurant owners closing their businesses due to the COVID-19 pandemic, lack of public awareness